The Relationship between Strategic Management and Organizational Effectiveness of Soft Drinks Manufacturers in Libya - Shalof, Mahmod Ramadan Ali (2010)
The strategic management process (SMP) is key part of the business success and organizational effectiveness. The SMP is comprised environmental analysis, strategy formulation, strategy implementation, and strategic control. This study investigates the relationship between strategic management process and organizational effectiveness of soft drinks manufacturer in Libya. Data were collected from executive in soft drinks manufacturer. Descriptive statistics were calculated and correlation analysis and regression analysis was used to test the hypothesized relationships. It was found that strategic management process has great impact and related to the organizational effectiveness.